EPIDEMIOLOGY AND CAUSES OF OPTIC ATROPHY IN GENERAL OUTPATIENT DEPARTMENT OF LUMBINI EYE INSTITUTE - Bajracharya, Kabindra; Gautam, Prachand; Yadav, Sanjeeb Kumar; Shrestha, Nirsara (Journal of Universal College of Medical Sciences, 2016)
INTRODUCTION: Optic atrophy is usually applied to the condition of the disc following degeneration of the optic nerve. The present study was done to explore the epidemiology and causes of optic atrophy. MATERIAL AND METHODS: A cross-sectional study of 100 cases of optic atrophy patients with convenience sampling was conducted from 1 July 2012 to 23 September 2012. Clinical history was taken including demography. Visual acuity was taken, pupillary reaction tested and posterior segment examined. Optic atrophy was diagnosed by optic disc examination with slit lamp bio-microscopy with aid of 90D lens. Disc pallor with diminution of vision was used as parameter to diagnose optic atrophy. RESULTS: Out of 100 patients, male were 54%. It was bilateral in 26%. The mean age was 53.6 years (+/-18.11 yrs SD). The highest occurrence was seen in 61-70 yrs age range. Glaucoma was the most common cause of optic atrophy involving 58%. Out of 42% non-glaucomatous optic atrophy, 55% manifested primary optic atrophy, 38% secondary optic atrophy and 7% consecutive optic atrophy. The non-glaucomatous causes were trauma, optic neuritis, central retinal vein occlusion, intracranial space occupying lesions, papilloedema and in nine cases cause was unknown. Socially blind patients comprised of 37%. CONCLUSION: Optic atrophy was nearly equal in occurrence in both male and female and common above 4th decade of life. Glaucoma was commonest cause. Non-glaucomatous optic atrophy was also not uncommon and several causal factors should be considered. Journal of Universal College of Medical Sciences (2015) Vol.03 No.02 Issue 10 Page: 26-29